Clinical outcomes of high-density mapping for atypical atrial flutter ablation. (3rd October 2022) - Abeln, B G S; Balt, J C; Klaver, M N; Maarse, M; Van Dijk, V F; Wijffels, M C E F; Boersma, L V A
Abstract: Background: High-density mapping is increasingly used in catheter ablation of complex arrhythmias. In atypical atrial flutters (AAFl), high-density mapping can provide a more accurate delineation of the arrhythmic circuit. This promotes acute procedural success, but follow-up data on clinical outcomes are scarce. Purpose: To study procedural characteristics and arrhythmia recurrence of high-density mapping-guided AAFl ablation. Methods: In this monocenter prospective observational cohort study, we included patients that were treated for AAFl using a high-density mapping system with a grid-patterned mapping catheter. We evaluated acute procedural success and atrial flutter recurrence at follow-up. Acute success was defined as non-inducibility of atrial flutters. Arrhythmia recurrence was defined by electrocardiographic documentation of atrial flutter. Results: Between April 2018 and July 2020, 65 patients (69% male; age 65±8yr; 69% prior PVI; 60% prior cardiac surgery) were included in this study. A total of 100 AAFl were observed during the procedures. The flutter circuit was unmappable for 14 flutters in 11 patients (17%). Critical isthmuses were identified and ablated in 32 patients (49%). Other ablation strategies included linear ablation lesions (i.e., roof in 25% of patients, box in 9%, anterior in 35%, left lateral mitral in 17%), re-PVI (11%), septal (8%) and right atrial (8%) ablation. Acute procedural success was achieved in 86% of the cohort. During a follow up of 1.5±0.7 years, 38% of the cohort had recurrence of an atypical atrial flutter for which 23% had a re-intervention (repeat flutter ablation in 11% patients and his ablation with pacemaker implantation in 14%). Atypical atrial flutter recurrence was associated with presence of an unmappable flutter (HR: 2.7, 95% CI [1.1–6.4], p=0.03) and critical isthmus ablation (HR: 0.40, 95% CI [0.17–0.93], p=0.03). Conclusions: Despite high-density mapping, 38% of patients had recurrence of an AAFl at follow-up. Presence of an unmappable flutter was associated with atrial flutter recurrence while critical isthmus ablation was associated with freedom from atrial flutter recurrence. Funding Acknowledgement: Type of funding sources: None.